Technique to reduce blood loss during open abdominal myomectomy: transverse or vertical incision? - Uzunlar,Ozlem (2021)
SUMMARY OBJECTIVE: To determine if there is a difference between uterine incision techniques (vertical vs. transversal) in terms of clinical results. METHODS: All women with leiomyomas who underwent open abdominal myomectomy (n=61) between March and August 2016 at the Gynecology and Obstetrics Clinic at the Women’s Health Research and Training Hospital Zekai Tahir Burak were included, and the clinical results were included and prospectively reviewed. RESULTS: The estimated blood loss during myomectomy increased in the transversal group compared with the vertical group (809.33±483.34 versus 405.32±180.95 mL, p<0.001). The average operation duration was 60 min, and the patients got discharged on the second day after surgery. No intergroup statistical differences were observed in the surgical procedure. CONCLUSIONS: Surgeons should give preference to the most viable incision depending on the size and location of the leiomyoma.